Characterization, testing, measurement, and metrology - Prakash, Chander; Singh, Sunpreet, 1989-; Davim, J. Paulo (Boca Raton, FL : CRC Press, 2021)
"This book presents the broad aspects of measurement, performance analysis, and characterization for materials and devices by advanced manufacturing processes. The field of measurement and metrology as a pre-condition for maintaining high quality products/devices/systems in materials and advanced manufacturing process applications has grown strongly over the past years. The focus of this book is to present in numerous technological sectors, smart materials in automotive, bio-manufacturing, chemicals, electronics, energy, and construction materials. The advanced materials, which are progressing nowadays, have novel properties, thus must be fully characterized and studied, in-depth, so they can be incorporated into products that out-perform existing problems. The book has capture emerging areas of materials science and advanced manufacturing engineering and presents the recent trends in research for young researchers, field engineers, and academic professionals"--
1. Mechanical Property Characterization of Construction Materials. 2. Evaluation of Material Surface Integrity. 3. Characterizations: SEM/FESEM, EDS, XRD, XPS, AFM, TEM, STEM, FTIR, DSC, TGA, DMA. 4. Mechanical Behaviour: Fracture, Damage, Fatigue. 5. Tribology and Wear. 6. Interfaces and Interphases. 7. Creep and Aggressive Environment. 8. Corrosion. 9. Measurement, Performance Analysis, and Characterization of Materials, Devices, and Systems using Advanced Technologies. 10. Characterization of Surfaces and the Relationship between Surface Properties and their Applications. 11. Surface Metrology -- Measurement and Characterization of Surface Topography including Functional Properties of Surfaces. 12. Measurement & Metrology in Materials and Advanced Manufacturing: Roughness, Forces, Corrosion, Wear, Crack Propagation and Fatigue. 13. Monitoring and Control of Machining/Manufacturing Processing of Advanced Materials. 14. Optimization of Machining/Manufacturing Processing. 15. Computational Intelligence: Neural, fuzzy, Genetic, and Swarm Particle Optimization. 16. Vision-Based Control and Control Engineering.
"Functional materials and advanced manufacturing" -- front cover.
OCLC-licensed vendor bibliographic record.
Keywords: Materials -- Testing; TECHNOLOGY / Manufacturing; TECHNOLOGY / Material Science